2008
DOI: 10.1063/1.2930680
|View full text |Cite
|
Sign up to set email alerts
|

Temperature acceleration of structural relaxation in amorphous Ge2Sb2Te5

Abstract: The structural relaxation (SR) process in an amorphous chalcogenide material (Ge2Sb2Te5) is studied by electrical measurements on phase-change memory devices. SR induces a change in the conduction regime from Poole to Poole–Frenkel transport, evidencing a temperature accelerated defect-annihilation process. Based on an Arrhenius kinetics with distributed activation energies, a temperature-acceleration law is shown, relating the time to reach a specific relaxed state to the temperature during isothermal experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 13 publications
3
67
0
Order By: Relevance
“…Since the data stability of phase-change devices relies on such physical properties, to describe the nature of structural relaxation is an important issue. Ielmini et al [19][20][21] examined the structural relaxation of the amorphous Ge 2 Sb 2 Te 5 by electrical measurements and suggested that the structural relaxation originates from the defect annihilation with a decrease in the concentration of localized states associated with structural disorder. Also, the development of the medium-range order in phase-change materials such as Ge 2 Sb 2 Te 5 ͑Ref.…”
Section: Resultsmentioning
confidence: 98%
“…Since the data stability of phase-change devices relies on such physical properties, to describe the nature of structural relaxation is an important issue. Ielmini et al [19][20][21] examined the structural relaxation of the amorphous Ge 2 Sb 2 Te 5 by electrical measurements and suggested that the structural relaxation originates from the defect annihilation with a decrease in the concentration of localized states associated with structural disorder. Also, the development of the medium-range order in phase-change materials such as Ge 2 Sb 2 Te 5 ͑Ref.…”
Section: Resultsmentioning
confidence: 98%
“…From previous publications [8][9][10] it is well known that the temporal dependence of the resistance drift in phase change memory devices can be described by a power law, R(t)=R 0 ⋅ (t/t 0 ) ν , with R 0 = R(t 0 ), the resistance at an arbitrary time t 0 and ν an empirical materials parameter. In thin films, however, the amorphous-as-deposited material has already undergone drift after deposition, prior to the beginning of the measurement.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to many other works [16,25,28,39,40], the resistance is measured directly during annealing in all the experiments performed within this work.…”
Section: Resistance Drift In Amorphous As-deposited Phase Change Filmsmentioning
confidence: 99%